Awareness of Female Students In Covering Their Intimate Parts Properly - Nihayatunnisa, Meisa; Febriani, Evi; Hasanah, Uswatun; Kumaidi, Muhamad (Peneliti.net, 2024)
Aurat is a member of the body that must be covered according to religion with clothing or the like according to their respective limits (women and men). Covering the aurat properly and in accordance with Islamic law must be done based on the student's self-awareness. If the aurat is opened intentionally then the culprit is sinful. Each of the women and men has aurat limits that have been set by Islamic law. Therefore, every Muslim and Muslimah is obliged to know the limits and then obey them by keeping their aurat in everyday life. Therefore, in this study the author wants to provide awareness to female students of the obligation to cover the aurat properly and in accordance with Islamic law and to provide ways to increase the awareness of female students in covering the aurat properly and in accordance with Islamic law. The problem discussed in this scientific paper is increasing the awareness of female students in covering the aurat properly which aims to determine the level of awareness of female students in covering the aurat properly outside the pesantren and how to increase the awareness of female students in covering the aurat properly and in accordance with Islamic law. This research uses library research, which uses the method of interviewing lecturers and female students at UIN RADEN INTAN LAMPUNG and with research methods using primary sources, namely in the form of books and journals relevant to this study. Based on the analysis conducted in this study, it is concluded that the level of awareness of female students in covering the aurat properly is still low and must be improved in order to be able to cover the aurat properly.